Research on the Construction of Gene Map and Digitization Path of Traditional Village dwellings Culture in Chongqing - Wei Yuan; Shi Jingyuan; Gao Yuxin (E3S Web of Conferences)
Traditional village residences are an important part of Chinese culture, but with the development of modernization, traditional villages are facing the dilemma of cultural inheritance. In order to protect and inherit traditional villages, this article uses the theory of cultural genes to collect and organize data on traditional village dwellings in Chongqing from multiple dimensions such as history, geography, and society. Cultural genes are classified and encoded to construct a cultural gene map of traditional village dwellings in Chongqing, in order to better understand and inherit the culture of traditional villages and dwellings. In addition, through the establishment of a multidimensional fusion of cultural gene mapping digital paths, we explore archival protection, revitalization, and inheritance methods with high precision and efficiency.